(untitled) (Revista Argentina de Cirugía, 2026)
Many devices have been described to collect the effluent from an enteroatmospheric fistula. We can summarize that devices can be manufactured or handmade, expensive or affordable, or vacuum assisted or not. Additionally, they may allow the patient to ambulate or may not assist with postoperative mobility. When facing this condition, several attempts are typically made to obtain a suitable device before discovering the right one for each individual patient. We present the case of a 60-yearold woman with an enteroatmospheric fistula successfully managed using Rivera’s condom technique.